The Shadow of Legality: A Critical Analysis of Unregistered Marriages (Nikah siri) in Islamic Jurisprudence - Sifa Salsabila; Nikmatur Rohmah (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
This study aims to examine the legal and social implications of nikah siri (unregistered marriages) in Indonesia, particularly regarding the protection of civil rights for women and children. The practice of nikah siri creates a conflict between Islamic law, which considers it valid, and state law, which does not recognise it, resulting in significant social and legal consequences. This qualitative research uses descriptive-analytical methods, including in-depth interviews, field observations, and documentation, and focuses on couples, religious leaders, and KUA officers. The study identifies three main findings: the separation between religious law and state law, with civil rights unprotected; economic and administrative barriers that drive individuals to choose nikah siri despite its legal risks; and the legal and social vulnerabilities of women and children born from nikah siri marriages. The research contributes to the field by integrating Islamic ethics, state law, and maqashid al-syari’ah to propose a more inclusive and ethical legal framework. It recommends reforms to reduce bureaucratic barriers and to promote the legal recognition of nikah siri marriages, safeguarding the rights of all parties involved.